Impact of Variant Reclassification in Cancer Predisposition Genes on Clinical Care. (2021) - Chiang, Jianbang; Chia, Tze Hao; Yuen, Jeanette; Shaw, Tarryn; Li, Shao-Tzu; Binte Ishak, Nur Diana; Chew, Ee Ling; Chong, Siao Ting; Chan, Sock Hoai; Ngeow, Joanne
Abstract : PURPOSE: Genetic testing has clinical utility in the management of patients with hereditary cancer syndromes. However, the increased likelihood of encountering a variant of uncertain significance in individuals of non-European descent such as Asians may be challenging to both clinicians and patients. This study aims to evaluate the impact of variant reclassification in an Asian country with variants of uncertain significance reported in cancer predisposition genes. METHODS: A retrospective analysis of patients seen at the Cancer Genetics Service at the National Cancer Centre Singapore between February 2014 and March 2020 was conducted. The frequency, direction, and time to variant reclassification were evaluated by comparing the reclassified report against the original report. RESULTS: A total of 1, 412 variants of uncertain significance were reported in 49.9% (845 of 1, 695) of patients. Over 6 years, 6.7% (94 of 1, 412) of variants were reclassified. Most variants of uncertain significance (94.1%, 80 of 85) were downgraded to benign or likely benign variant, with a smaller proportion of variants of uncertain significance (5.9%, 5 of 85) upgraded to pathogenic or likely pathogenic variant. Actionable variants of uncertain significance upgrades and pathogenic or likely pathogenic variant downgrades, which resulted in management changes, happened in 31.0% (39 of 126) of patients. The median and mean time taken for reclassification were 1 and 1.62 year(s), respectively. CONCLUSION: We propose a clinical guideline to standardize management of patients reported to have variants of uncertain significance. Management should be based on the patient's personal history, family history, and variant interpretation. For clinically relevant or suspicious variants of uncertain significance, follow-up is recommended every 2 years, as actionable reclassifications may happen during this period.